31P Development of a biomarker-based calculator to predict the probability to achieve a pathologic complete response after neoadjuvant pembrolizumab in muscle-invasive bladder cancer. (15th December 2019) - Marandino, L; Bandini, M; Madison, R; Raggi, D; Gallina, A; Colecchia, M; Lucianò, R; Giannatempo, P; Farè, E; Pederzoli, F; Bianchi, M; Colombo, R; et al.
Abstract: Background: The PURE01 study (NCT02736266) evaluates preoperative pembrolizumab before radical cystectomy (RC). Here, the possibility to predict the pathologic complete response (pT0) after neoadjuvant immunotherapy could have paradigm-shifting implications for the management of patients with MIBC. Methods: The reported analyses include comprehensive genomic profiling with FoundationONE CDx assay and programmed cell-death-ligand-1 (PD-L1) combined positive score (CPS, Dako 22C3 antibody) on baseline TURB samples. Multivariable logistic regression analyses (MVA) evaluated clinical T-stage and biomarkers (tumor mutational burden [TMB], and CPS) in association with pT0 response. Multivariable-derived coefficients were used to develop a novel risk calculator. Decision-curve analysis was used to evaluate the net benefit of the predictive model. Results: From 02/2017 to 06/2019, 112 patients with full biomarker data were enrolled. At MVA, only CPS showed a significant association with pT0 (p = 0.005). Increasing TMB and CPS values featured a linear association with logistic pT0 probabilities (p = 0.02 and p = 0.004). Very high TMB values, associated with a predicted probability of pT0 > = 55%, were independent from CPS contribution. The coefficients of the predictive model were used to develop a risk calculator. The c-index of the model was 0.77. At decision-curve analysis, the net-benefit of the model was higher than the "treat-all" option from more than 10% threshold probabilities. Conclusion: We presented the first biomarker-based risk stratification tool that can be used to recommend use of neoadjuvant pembrolizumab in those patients who have equal or greater chances to achieve a pT0 status compared to the literature on neoadjuvant chemotherapy or to RC alone, depending on cisplatin eligibility. Clinical trial identification: PURE01 study (NCT02736266). Legal entity responsible for the study: The authors. Funding: Merck & Co., Inc., Kenilworth, NJ, USA; Associazione Italiana per la Ricerca sul Cancro (AIRC). Disclosure: R. Madison: Shareholder / Stockholder / Stock options, Full / Part-time employment, employee and stock owner of Foundation Medicine Inc: Foundation Medicine Inc. M. Colecchia: Speaker Bureau / Expert testimony: Roche Diagnostics. S.M. Ali: Full / Part-time employment: Foundation Medicine. J.H. Chung: Full / Part-time employment: Foundation Medicine. J. Ross: Leadership role, Research grant / Funding (institution), Shareholder / Stockholder / Stock options, Full / Part-time employment: Foundation Medicine. A. Salonia: Speaker Bureau / Expert testimony: Astellas Pharma; Travel / Accommodation / Expenses: Konpharma. A. Briganti: Advisory / Consultancy: Astellas Pharma; Advisory / Consultancy: Hanssen-Cilag; Advisory / Consultancy: OPKO Health; Advisory / Consultancy: MDxHealth; Advisory / Consultancy: Ferring; Research grant / Funding (institution): Novartis. A. Necchi: Advisory / Consultancy: Merck, Incyte, AstraZeneca, Roche, Rainier Therapeutics, Clovis Oncology, Bristol-Myers Squibb, Bayer, Basilea Pharmaceutica; Research grant / Funding (institution): AstraZeneca, Ipsen, Merck and Incyte; Spouse / Financial dependant: Bayer. All other authors have declared no conflicts of interest.